Methodological Principles of Teaching The Science of "Education" In Primary Classes (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Abstract. In this article, the use of pedagogical technology in the classroom, interactive methods and educational games in primary school, the use of modern information and communication technologies in teaching elementary education in primary school helps students to think independently, creative research and logical thinking. along with the expansion, ideas are articulated that help them relate what they learn in the lessons to life, increasing their interest.